Paradigm of Post Positivism, Critical Theory, and Constructivism in Social Research - Puspasari, Shafa’ Annisa; Sary, Intan Umull Magfira; Winarno, Agung (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to explore the application of post-positivism, critical theory, and constructivism paradigms in social research in the field of management. The method used in this study is a qualitative approach with descriptive and analytical data analysis, through the elaboration of main ideas related to the topic discussed. The results of the study indicate that the three paradigms, namely post-positivism, critical theory, and constructivism, all strive to advance science, although with different approaches. However, in essence, the three paradigms complement each other in providing a deeper and contextual understanding of managerial practices, as well as opening up opportunities for a more inclusive, fair, and socially dynamic managerial approach in the organization. The application of these three paradigms also encourages changes in the way of viewing roles and power in the organization, which can lead to improvements in overall managerial practices.